Assessment of influencer’s effects on customers’ online purchasing behavior in Vietnam - Pham Minh (HO CHI MINH CITY OPEN UNIVERSITY JOURNAL OF SCIENCE, 2021)
Today, the development of the Internet and social networks has changed the lives of human beings. The ability of these technologies to connect people in real-time expands the influence of some people in the community. Therefore, this study is conducted to test whether customers change purchasing behavior in online environments under the impact of those influencers by using Technology Acceptance Model (TAM). The study conducted a survey of 503 Vietnameses on Google Form from November 2020 to mid-January 2021. The collected data were analyzed using AMOS 24 with CB-SEM analysis method. The results showed a positive relationship between influencers and customers’ online purchasing behavior. More specifically, customers are more likely to buy online if they trust influencers and their advertisements. This is the most influential factor among the three influencer traits (as source credibility): trustworthiness, expertise, and attractiveness. A remarkable point in this study is that Vietnamese people are more concerned with perceived ease of use when buying online than other factors in the TAM model. This is the basis for businesses to implement influencer marketing strategies and improve the competitiveness of their online business.